Morphology and assessment of genetic structure and diversity of Dionysia revoluta (Primulaceae) in Iran - SIMIN YOUNESI; MOSTAFA ASSADI; TAHER NEJADSATTARI; IRAJ MEHREGAN (Biodiversitas Journal of Biological Diversity, 2017)
Younesi S, Assadi M, Nejadsattari T, Mehregan I. 2017. Morphology and assessment of genetic structure and diversity of Dionysia revoluta (Primulaceae) in Iran. Biodiversitas 18: 1173-1178. Dionysia revoluta Boiss. (Primulaceae), the most widespread species of the genus in Zagros Mountains of western Iran, is studied morphologically and genetically. Clustering analysis of morphological characters did not match the biogeography of the populations. Cluster analysis separated two subspieces of D. revoluta i.e. subsp. revoluta and subsp. canescens (Boiss.) Wendelbo. Factor analysis (FA) showed that petal size and length of the corolla tube were the only two factors with the slightest variation. Amplified Fragment Length Polymorphism (AFLP) fingerprint technique was used to evaluate the genetic structure and diversity among 14 populations of D. revoluta. The results of AFLP analysis of D. revoluta individuals showed that 67% of the total diversity was that of within-population diversity, 17% was among-population diversity and 16% was among-region diversity. AFLP data suggest that amount of genetic variation of populations growing in localities with other Dionysia species in sympatry is higher than those populations growing allopatric. This implies the hybridization as a possible important factor in the evolution of the group. It was also concluded that hybridization would result in higher genetic diversity within those populations of D. revulota occur with other species in sympatry.